SUSTAINING WAYANG TOPENG MALANGAN (MALANG TRADITIONAL PUPPET MASK DANCE) THROUGH ASMOROBANGUN'S STRATEGIES - Fitriyani, Fitriyani; Rofiaty, Rofiaty; Susilowati, Christin (Jurnal Aplikasi Manajemen, 2019)
This study aims to see the strategies of Asmorobangun art studio in preserving the existence of Wayang Topeng Malangan. This study uses the descriptive qualitative method with phenomenology approach. Phenomenology shows a philosophical approach to understand human experience based on the idea that human experience can not be separated from their subjectivity itself and it is determined by the context in which human lives (Zigmund and Babin, 2007: p.136). The finding shows that in terms of maintaining the existence of Wayang Topeng Malangan, Asmorobangun art studio applies these following strategies: 1). Shortening the dance performance; 2). Developing the marketing media using the internet; 3). Product diversification of Topeng Malangan Souvenirs; and 4). Providing a learning lesson about Wayang Topeng Malangan.